Development of economic MeV-ion microbeam technology at Chiang Mai University - Singkarat S. (2017)
© 2017 Elsevier B.V. Developing high technologies but in economic manners is necessary and also feasible for developing countries. At Chiang Mai University, Thailand, we have developed MeV-ion microbeam technology based on a 1.7-MV Tandetron tandem accelerator with our limited resources in a cost-effective manner. Instead of using expensive and technically complex electrostatic or magnetic quadrupole focusing lens systems, we have developed cheap MeV-ion microbeams using programmed L-shaped blade aperture and capillary techniques for MeV ion beam lithography or writing and mapping. The programmed L-shaped blade micro-aperture system consists of a pair of L-shaped movable aperture pieces which are controlled by computer to cut off the ion beam for controlling the beam size down to the micrometer order. The capillary technique utilizes our home-fabricated tapered glass capillaries to realize microbeams. Either system can be installed inside the endstation of the MeV ion beam line of the accelerator. Both systems have been applied to MeV-ion beam lithography or writing of micro-patterns for microfluidics applications to fabricate lab-on -chip devices. The capillary technique is being developed for MeV-ion beam mapping of biological samples. The paper reports details of the techniques and introduces some applications.